Survivor my life as a Rohingya refugee - Ziaur Rahman 1974- (Gerakbudaya Enterprise, supported by the Al-Ikhlas Hope Society, 2021)
Having fled from Myanmar at a young age, Ziaur Rahman's story is one of survival. From the heavily controlled regime of the refugee camps in Bangladesh, bleak depths of the sea, and the Covid-19 crisis, the politics of being a refugee are explored in this deep, immensely personal narrative.